Mixed Value Problem for a One-Dimensional Nonlinear Nonstationary Twelve moment BoltzmannS System Equations with the Maxwell-Auzhan Boundary Conditions (Global Journal of Science Frontier Research, 2020)
It is proved existence and uniqueness of solution of the problem with initial and boundary conditions of Maxwell-Auzhan (we consider pure specular reflection from the boundary) for the nonstationary nonlinear one-dimensional Boltzmann's twelve-moment system equations in space of functions continuous in time and summable in square by spatial variable.
Keywords: Boltzmann's homogeneous one-dimensional equation; Boltzmann’s moment system equations